Application of Traffic Ethics to Instill Disciplined Driving Behavior - Alya Najmi Putri Arifin; Belia Fasra; Sifa Nur Inayah; Tasya Avionita; Ahmad Fuadin (CV. Rayyan Dwi Bharata, 2023)
This study examines traffic ethics for students of the social science education faculty at the Indonesian University of Education, which aims to find out whether traffic ethics has been applied and whether the provisions are correct. Is it important to apply this ethic in traffic that we often see on the highway and whether it will result in obedience to every citizen. This research uses a survey method (survey research) with a descriptive design. This data collection method was carried out by distributing questionnaires taken from 100 students which showed that students of the social science education faculty at the Indonesian University of Education were categorized as adhering to traffic ethics. The participants in this study were students of the social sciences education faculty at the Indonesian University of Education. From the results of the questionnaire with the background of the students of the social sciences education faculty at the Indonesian University of Education, namely (1) use ethics when driving. (2) Obey traffic rules.